Stepping into the 60s: Tomas Kuhn’s intellectual turn towards the Philosophy of Science - Melogno, Pablo; Courtoisie, Agustín (Daimon Revista Internacional de Filosofia, 2019)
In 1975 Kuhn publishes The Copernican Revolution, and in 1962 The Structure of Scientific Revolutions. Most commentators believe both works to be an expression of the same philosophical project. Against this interpretation, we argue that there is a lack of continuity between both books, arising from the fact that between 1957 and 1958 Kuhn comes into contact with the works of Hanson, Wittgenstein and Feyerabend, whose influence marks a break from his previous work. We also suggest that in 1957 Kuhn applies a casuistical historiography, and, in 1962, a structural historiography. We conclude that there is no relationship of continuity between Kuhn’s first two works.